Gander, innovation and education in Latin America / Ingrid Jung and Linda King - Jung, Ingrid (México, 1999)
Theoretical considerations, gender based non- formal education projects
Col. Educ
Keywords: 1. EDUCACIÓN 2. INNOVACIÓN EDUCACIÓN